Triangle Inequality states that for any real numbers *a* and *b*,

|*a*| + |*b*| ≥ |*a* + *b*|.

In proving this theorem, we use the definition of absolute value of a number. The absolute value of a number is *x* if *x* *>* 0 (*), –*x* if *x* < 0 (**) and 0 if *x* = 0 (**). For instance, the absolute value of 5 is 5 since 5 > 0. On the other hand, the absolute value of -3 is -(-3) = 3. Clearly, the absolute value of 0 is 0. The geometric representation of triangle inequality is shown above (see Demystifying Triangle Inequality). It states that a triangle can only be formed if the combined length of any two sides is greater than that of the third sides. Using the definition of absolute value, we now prove the theorem. **Theorem** For any real numbers a and b, |*a*| + |*b*| ≥ |*a* + *b*|.

**Proof**

*Case 1: a and b are positive* If *a* and *b* are both positive, then *a* + *b* and |*a* + *b*| are also positive. From *,

|*a*| + |*b*| = *a* + *b* = |*a* + *b*|.

*Case 2 : a and b are both negative* If *a* and *b* are both negative, from **, |*a*| + |*b*| = (-*a*) + (-*b*) = -(*a* + *b*) But from **, |*x*| = –*x* if *x* <0, so -(*a* + *b*) = |*a* + *b*| which means that

|*a*| + |*b*| = |*a* + *b*|.

*Case 3: a is positive and b is negative* |*a*| + |*b*| = *a* + (-*b*) and |*a* + *b*| is *a* + *b* itself (if positive) or –(*a* + *b*) if negative. But, *a* > –*a* and – *b* > *b* (why?) so,

*a* + (-*b*) > *a* + *b* and (-*a*) + (-*b*) > -(*a* + *b*).

In either case, we have |*a*| + |*b*| > |*a* + *b*|. Therefore, combining the three cases, we have

|*a*| + |*b*| ≥ |*a* + *b*|.

Pingback: The Proof of the Hinge Theorem - Proofs from The Book